The impasses of community participation in the community council at a Rural School in the municipality of Placa/PA - Irlanda do Socorro de Oliveira Miléo; Raquel da Silva Lopes; Marcos Marques Formigosa; Josicley Silva Carneiro (Universidade Federal do Norte do Tocantins, 2022)
This article has as object of study the School Council, understanding this as a fundamental mechanism in the process of building and experiencing democratic practices. It seeks to reflect how the participation of the School Council members takes place in the deliberative and supervisory processes regarding the decisions that guide school practices, in order to analyze how the counselors, position themselves regarding participation in the decision-making processes regarding the improvement of teaching in a public school of the field in the Municipality of Placa/PA. The methodological approach is of an exploratory qualitative nature with data collected through individual interviews with five members of the School Council of a rural school located in the Terra Prometida community. The results point to the need for greater action by the counselors regarding the monitoring of educational practice in the investigated school, since this institution does not yet have the pedagogical project, an aspect that compromises the teaching of the rural school, at the same time that it signals a disregard for both the management of the school-pole and the Council itself, which can be caused by lack of information and training of those involved.